Investigando caminhos para a introdução da Avaliação da Sustentabilidade Absoluta em compras sustentáveis de alimentos: apresentando o Food Procurement with a focus on absolute environmental sustainability assessment (FP-AESA) - Akim, Erica Kushihara (Universidade Federal de São Carlos, 2026)
Food production and consumption systems represent a major driver of planetary boundary transgressions. In this scenario, sustainable procurement decisions can act as mechanisms to promote food systems that respect Earth’s carrying capacity. Therefore, the objective of this thesis was to propose a framework to introduce Absolute Environmental Sustainability Assessment (AESA) as a strategy for managing planetary boundaries within the sustainable food procurement process. The proposed model, named FP-AESA (Food Procurement with a focus on absolute environmental sustainability assessment), was structured around two perspectives: a simplified approach and an in-depth approach. To this end, the research comprised an exploratory literature review, followed by two case studies - one on food consumption in Brazil and another on meals served at a university restaurant - in addition to the validation of the framework by experts via the Fuzzy Delphi Method (FDM). The review results indicated that Equal Per Capita (EPC) distributive justice is the most widely adopted allocation principle (52%) for the safe operating space in food AESA. Regarding the case studies, applying the simplified approach to Brazilian household consumption data revealed that the transgression of planetary boundaries is more severe in the freshwater use category than in climate change. Within this scale of Brazilian domestic consumption, beef recorded the highest transgression rates, whereas rice and eggs showed greater adherence to sustainable boundaries. In turn, the AESA under the in-depth approach, applied to the university restaurant scenario, identified ten critical processes, highlighting the Climate Change and Freshwater Eutrophication categories, whose impacts exceeded sustainability thresholds, driven mostly by beef and rice consumption. It was found, therefore, that different AESA results can be observed depending on the framework version applied, the carrying capacity reference adopted, and the chosen sharing principles. Finally, validation via FDM indicated that, despite resource and technical knowledge limitations, the strategic review and continuous learning stages of the model achieved a high level of consensus among experts. In summary, the application of these approaches demonstrates how to introduce planetary boundaries into sustainable procurement management, provided that the trade-offs and methodological uncertainties intrinsic to the process are considered. For management and public policy formulation, this research exemplifies the feasibility of adopting measurable and validated absolute sustainability criteria, which can be integrated to promote food security within planetary boundaries. This thesis presents a theoretical contribution by proposing a framework to integrate AESA into the sustainable procurement process for food and food services.
Investigating pathways for introducing Absolute Sustainability Assessment into sustainable food procurement: presenting the Food Procurement with a focus on absolute environmental sustainability assessment (FP-AESA)
Keywords: Avaliação da Sustentabilidade Ambiental Absoluta; Compras sustentáveis; Sistemas alimentares; Limites Planetários; ISO 20400; Sustainable procurement; Absolute Sustainability Environmental; Food systems; Planetary Boundaries; ISO 20400; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; 12. Consumo e Produção Responsáveis; 2. Fome Zero e Agricultura Sustentável; 13. Ação contra a Mudança Global do Clima